Sow Vaccination with a Protein Fragment against Virulent Glaesserella (Haemophilus) parasuis Modulates Immunity Traits in Their Offspring - López-Serrano, Sergi (Vaccines (Basel), 2021)
Glaesserella (Haemophilus) parasuis, an early colonizer of the nasal cavity in piglets, is a highly heterogeneous species, comprising both commensal and virulent strains. Virulent G. parasuis strains can cause fibrinous polyserositis called Glässer’s disease. Colostrum is a source of passive immunity for young piglets. When vaccinating sows, protective antibodies are transferred to their offspring through the colostrum. Here, sow vaccination was performed with a protein fragment, F4, from the outer membrane trimeric autotransporters VtaAs exclusively found in virulent G. parasuis. Piglets were allowed to suckle for 3 weeks, following which a challenge with two virulent strains of G. parasuis was performed. A group of nonvaccinated sows and their piglets were included as a control. Antibodies against F4 were confirmed using ELISA in the vaccinated sows and their offspring before the G. parasuis challenge. Compared to the control group, F4-vaccination also resulted in an increased level of serum TGF-β both in vaccinated sows and in their offspring at early time points of life. After the challenge, a lower body temperature and a higher weight were observed in the group of piglets from vaccinated sows. One piglet from the non-vaccinated group succumbed to the infection, but no other significant differences in clinical signs were noticed. At necropsy, performed 2 weeks after the virulent challenge, the level of surfactant protein D (SP-D) in bronchoalveolar lavage was higher in the piglets from vaccinated sows. Vaccination did not inhibit the nasal colonization of the piglets by the challenge strains.